Forced Oscillation Detection Amid Communication Uncertainties - Tossaporn Surinkaew; Rakibuzzaman Shah; N. Mithulananthan; S. M. Muyeen; Kianoush Emami; Issarachai Ngamroo (IEEE Systems Journal, 2021)
This article proposes a novel technique for the detection of forced oscillation (FO) in a power system with the uncertainty in the measured signals. The impacts of communication uncertainties on measured signals are theoretically investigated based on the mathematical models developed in this article. A data recovery method is proposed and applied to reconstruct the signal under the effects of communication losses. The proposed FO detection with communication uncertainties is evaluated in the modified 14-machine Southeast Australian power system. A rigorous comparative analysis is made to validate the effectiveness of the proposed data recovery and FO detection methods.
Keywords: Power System Optimization and Stability; Power System Reliability and Maintenance; Optimal Power Flow Distribution